EFEKTIFITAS KEGIATAN EMPOWERMENT EDUCATION DALAM MENINGKATKAN SELF EFFICACY PASIEN KANKER PAYUDARA DI RS.UMUM KOTA MAKASSAR - Evi Lusiana; Muh. Zukri Malik; Suriyani Suriyani (Journal of Islamic Nursing, 2020)
Breast cancer is a problem that often occurs in women both in developed and developing countries. For this reason, it is necessary to prevent the increasing mortality rate, one of which is by increasing self-efficacy which can be achieved by providing advice, information and motivation with empowerment education. Based on this, the researchers conducted this study with the aim of knowing the effect of empowerment education in increasing the self-efficacy of breast cancer patients. The research method used is a quantitative study with a one group test approach. The results obtained are from 5 (five) items of self-efficacy, 3 (three) items that have changed, namely self-confidence in getting information about illness / complaints experienced (p: 0.023), receiving help from the community, family and friends (p. : 0.02), and treats breast cancer disease and symptoms (0.041). Based on these results it can be concluded that empowerment education activities should be one of the activities of providing nursing interventions to breast cancer patients.Keywords: Empowerment Education; Self Efficacy; Breast cancer